Multi-functional concrete with recycled aggregate (2022)
Pervious Concrete (PC) pavement is one of the most prevalent Sustainable Urban Drainage Systems (SUDS) used to decrease the risk of flooding, allow the natural disposal of water through infiltration and reduce the pollution of watercourses. The use of agricultural waste and collapsed buildings rubbles are reported to improve the properties of conventional concrete. However, their use in PC has not been fully explored. This study was designed to investigate the effect of Sorghum Husk Ash (SHA) on the properties of Recycled Concrete Aggregates (RCA) PC. Sorghum husk was incinerated at 700°C for three hours to produce SHA. The chemical composition of SHA was determined using an X- ray fluorescence analyzer. Rubbles of collapsed buildings were crushed to smaller sizes for physical and mechanical tests [specific gravity, water absorption, bulk density, void ratio, aggregate crushing value (ACV), and aggregate impact value (AIV)] and sieved to between 9.50 and 4.75 mm for PC production. Mix proportioning was done following ACI specifications. Mixtures of PC were prepared at various replacement levels (0, 5, 10, 15, 20, and 25%) of cement with SHA using 100% RCA. These were molded into 100 mm (height) x 200 mm (diameter) cylindrical samples. The prepared samples’ density, compressive strength, porosity, and permeability was determined at 28-day of curing using ACI standards. The properties were correlated using regression equations in Microsoft Excel Software 2013. The adequacy of adopted equations was determined using the coefficient of determination (R2). The sum of percentages (77.3%) of silica, alumina, and ferric oxide was obtained for SHA, which is over 70% requirement of a pozzolan. Suitable result was obtained for physical and mechanical [specific gravity (2.53), water absorption (2.8%), bulk density (1301 kg/m3), void ratio (48.58%), ACV (26.96%), and AIV (24.02%)] properties of RCA. The density and compressive strength of RCA-PC respectively reduces from 1748 - 1715 kg/m3 and 7.78 - 4.05 N/mm2 while the porosity and permeability increase from 24.06 - 28.11% and 8.71 - 13.86 mm/s as the percentage replacement of SHA increases from 5 - 25%. The recorded compressive strength for all the mixtures was within the ACI acceptable specification (2-28 N/mm2). Increasing the contents of SHA significantly enhanced the porosity and permeability of PC, while the optimum compressive strength was obtained at 5%. The R2 of regression equations (0.90-0.99) indicates good correlations among the PC properties. It is concluded that SHA pozzolan and RCA are suitable for the production of PC for SUDS.